Potential role of cannabidiol for seizure control in a patient with recurrent glioma. (January 2020) - Hsu, Kristin; Whitham, Emma; Kichenadasse, Ganessan
Highlights: Glioma-related epilepsy can be difficult to treat. There has been increasing interest in medicinal cannabis (or cannabidiol or CBD) as an anti-epileptic drug. CBD could potentially be a management option in treatment-refractory epilepsy in glioma patients. It is unclear if CBD has anti-tumour effects but more studies should be undertaken to explore this effect. Abstract: Glioma-related epilepsy significantly impact on patients' quality of life, and can often be difficult to treat. Seizures cause significant morbidity for example neurocognitive deterioration, which may result from seizures themselves or due to adverse effects from antiepileptic drugs. Management of tumour with surgery, radiotherapy and chemotherapy may contribute to seizure control, but tumour related epilepsy is often refractory despite adequate treatment with standard anti-epileptic medications. Given the increasing interest in medicinal cannabis (or cannabidiol or CBD) as an anti-epileptic drug, CBD may help with seizure control in glioma patients with treatment-refractory seizures. Here we present a case of a young lady with recurrent glioma who had refractory seizures despite multiple anti-epileptic agents, who had significant benefit with CBD.